Contribuições da mediação ambiental internacional para paz sustentável: experiência da unidade de apoio à mediação da ONU (MSU) - Cardoso, Simone Alves (2017)
Given the multiplicity of interaction between environment, development and security, it is necessary to build solutions that can act in front of this complex, dynamic and flexible scenario. This research examines whether international environmental mediation, encouraged by the UN Mediation Support Unit at conflicts involving natural resources, can be considered an effective and adequate international environmental governance tool for sustainable and inclusive peace consolidation. This concern is justified, because sustainable development and environmental peace are interdependent and constitute today one of the greatest challenges of humanity. For a better understanding of this scenario, International Environmental Law was highlighted, indicating its characteristics and relation with international environmental governance. Governance, as a reflection of global society, broadens participation in decision-making processes, as it promotes action among states, civil society, governmental and non-governmental organizations, which is a striking feature of environmental pacification. The theoretical study of conflict and the identification of mediation models and mediators' actions are fundamental to understanding how mediation will contribute to the construction of sustainable peace. In this context, the analysis of the Mediation Unit has proved to be an example of networking among several mediators, such as UN, universities, non-governmental organizations, among others, in the construction of consensual solutions through mediation. All the actors involved in this network contributed to the formation and consolidation of the fundamental guidelines for the development of mediation around natural resources. This interaction led to the formation of an epistemic community of scholars between the interaction of peace and conflict, as well as a community of practice that integrates the UN into a network of mediators. In this regard, the UN, through the Mediation Support Unit, has been positioned as the manager of this knowledge network, concentrated in its database information, which is generated by several researchers, who strive to provide a theoretical basis for the pacification strategies, along with the experts in mediation field, who have the practical basis. Mediation promotes consensual peace, which is based on the construction of agreements that put an end to violence and hostilities. In addition, it establishes a new relationship founded on harmonic interaction aimed at achieving mutual goals, in order to reach a fair distribution of benefits and also of a reciprocal identity. With more peace-keeping efforts based on theory validated by research and translated into practical procedures, more effective and longer lasting peace will tend to be.